Understanding BIM Adoption in the AEC Industry: The Case of Jordan - Btoush, Mohammed; Ahmad Tarmizi, Haron (IOP Publishing, 2017)
Building information modelling (BIM) is a new and powerful technology implemented by many countries. The construction industry in Jordan plays a vital role and contributes immensely to the economic growth and development. In order to boost the industry and the economy, many industry players including engineers and contractors have recommended the implementation of BIM in Jordan. However, research demonstrates that successful BIM implementation is possible through the awareness of the different levels of BIM, which is a basic precondition for BIM implementation. Without a clear understanding of BIM, many companies would be unable to fully achieve BIM potentials or implement BIM in their building lifecycle. The objective of this study is to assess the current awareness of BIM technology in the Jordanian construction industry. A field interviews were conducted and 15 responses were collected and. The findings indicate that a significant proportion of respondents have little or no understanding of the concept of BIM. Also, the usage was found to be very low. Based on the results, a holistic roadmap was developed to spread the BIM adoption through the Jordanian construction industry. It is expected that this roadmap would lead to a better understanding and enable the industry towards more extensive implementation of BIM.